ECMS 2022 Proceedings Edited by Ibrahim A. Hameed, Agus Hasan, Saleh Abdel-Afou Alaliyat 2022
DOI: 10.7148/2022-0174
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Predicting the Amount of Photosynthetically Available Radiation from BGC-ARGO Float Observations in the Water Column

Abstract: Modern oceanography uses, amongst other platforms, automated diving devices, which are drifting with the ocean current whilst continuously collecting vertical profiles of environmental parameters. One of the important parameters is photosynthetically available radiation (PAR). It was studied in this work whether the PAR values can be reconstructed by combinations of measurements from the remaining onboard sensors with specific wavelength. If a reconstruction of PAR is possible, this would allow allocating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Pioneering work by [26] showed that global 3D reconstruction of the b bp could be performed thanks to the development of the first SOCA model. More recently, subsets of irradiance data (ED380, ED412, and ED490) acquired by BGC-Argo floats have been used to predict PAR either through statistical approaches [59] or the use of neural networks [60].…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work by [26] showed that global 3D reconstruction of the b bp could be performed thanks to the development of the first SOCA model. More recently, subsets of irradiance data (ED380, ED412, and ED490) acquired by BGC-Argo floats have been used to predict PAR either through statistical approaches [59] or the use of neural networks [60].…”
Section: Discussionmentioning
confidence: 99%